Salivary protein quantification among periodontitis patients with different disease severity: a pilot study - Neelambigai R,; Poonisha Nsk,; Nurrul Shaqinah N,; Shahida Ms,; Nik Madihah Na,; Farinawati Y, (Penerbit UKM, 2023)
The salivary protein quantification reflecting the periodontal pathophysiology among patients with different periodontitis severity has not been well explored. This quantification is fundamental as the changes in the quantity of proteins in different severities of periodontitis can reflect the periodontal complex alterations. This pilot study aimed to quantify and compare the salivary proteins by collecting unstimulated saliva from periodontitis patients and healthy individuals. The radioimmunoprecipitation assay (RIPA) protocol was used to extract protein from patients’ saliva and quantified using the Nanodrop Spectrophotometer 2000/2000c (A280) set at 280 nm wavelength. The mean concentration of salivary proteins was shown to be 26.48 + 2.95 mg/mL in healthy patients, 22.00 + 0.38 mg/mL in Stage 1 periodontitis patients, 27.34 + 1.61 mg/mL in Stage 2 periodontitis patients, 27.11 + 0.66 mg/mL in Stage 3 periodontitis patients and 24.89 + 1.91 mg/mL in Stage 4 periodontitis patients. However, the mean difference between all groups was not statistically significant. Within the limitations of this study, there was no difference in the salivary protein quantity among patients with different stages of periodontitis.